Legal "Cobwebs": A Recursive Model of the Market for New Lawyers - Freeman, Richard B. (The Review of Economics and Statistics, 1975)
THE market for new law school graduates has undergone considerable change in recent years, with starting salaries increasing rapidly following the enormous increase in rates of the major New York firms in 1968' and enrollments into law programs skyrocketing in the late 1960's. What explains these and earlier developments in the market for new lawyers? Does the influx of students reflect economically responsive supply behavior with respect to salary and other labor market incentives? What factors underly changes in the salaries of starting lawyers? This paper investigates these questions with a variant of the recursive model of the market for highly-trained workers originally used to analyze engineering shortages and surpluses (Freeman, 1971). Application of the model to a profession which differs substantially from engineering and related sciences but has a similar fixed time delay in producing new specialists provides a test of its general validity, as well as insight into the operation of the legal labor and education markets. This paper begins with a brief description of the empirical phenomenon under study -patterns of change in the number of law students, legal salaries, and activity in the profession. Section II develops a recursive cobweb-type model to explain these developments. Section III presents estimates of the supply and salary equations of the model. The final section examines the endogenous cyclic fluctuations in the market and summarizes the major findings.